2018
DOI: 10.1371/journal.pone.0207150
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of prodromal symptoms and schizophrenia-spectrum personality disorder traits by positive and negative schizotypy: A 3-year prospective study

Abstract: The present study extends previous cross-sectional findings by examining the predictive validity of positive and negative schizotypy in a young adult sample at a three-year follow-up. Schizotypy and schizophrenia share a comparable multidimensional structure with positive and negative dimensions being the most strongly supported factors. Previous cross-sectional and longitudinal studies employing the psychometric high-risk strategy indicated that schizotypy is a useful method for identifying risk and resilienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 62 publications
5
13
0
Order By: Relevance
“…Consistent with previous interview studies (e.g., Kwapil et al, 2008; Racioppi et al, 2018), both positive and negative schizotypy were associated with dimensional ratings of schizotypal and paranoid personality traits—although they have opposing patterns of association with schizoid traits. However, to our knowledge, previous studies did not decompose these findings to determine whether positive and negative schizotypy were associated with the same traits or with different traits within the same personality disorder.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with previous interview studies (e.g., Kwapil et al, 2008; Racioppi et al, 2018), both positive and negative schizotypy were associated with dimensional ratings of schizotypal and paranoid personality traits—although they have opposing patterns of association with schizoid traits. However, to our knowledge, previous studies did not decompose these findings to determine whether positive and negative schizotypy were associated with the same traits or with different traits within the same personality disorder.…”
Section: Discussionsupporting
confidence: 88%
“…Structured interviews provide a useful method for assessing schizotypy and evaluating the validity of schizotypy scales, although other researchers have noted the limitations of diagnostic interviews (e.g., Chmielewski et al, 2015; Samuel et al, 2011; Samuel et al, 2016). Cross-sectional and longitudinal interview studies have demonstrated the validity of the WSS (e.g., Bolinskey et al, 2017; Chapman et al, 1994; Cicero et al, 2014; Gooding et al, 2005; Kwapil, 1998), and its positive and negative schizotypy dimensions (e.g., Barrantes-Vidal et al, 2013; Gross et al, 2015; Kwapil et al, 2008; Kwapil et al, 2013; Racioppi et al, 2018). These studies demonstrated that positive schizotypy is associated with psychotic-like symptoms, schizotypal and paranoid personality traits, impaired functioning, and mood disorders and substance abuse.…”
Section: Psychometric Assessment Of Schizotypymentioning
confidence: 99%
“…The multifaceted and complex portrait obtained in the present study provides valuable information on broad aspects of the psychological functioning of CHR individuals. Looking at this picture as a Gestalt, it seems to tap into different dimensions of the schizotypy construct (47). The schizotypy construct refers to the continuum of positive, negative, and disorganized psychotic-like signs and symptoms, ranging from healthy to pathological, that has been theoretically considered-and empirically demonstrated-to predict schizophrenia-spectrum disorders (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Other reports also quite early suggested that schizotypy indicates proneness to schizophrenia ( 3 ) and schizophrenia-spectrum personality disorders ( 4 ). Since these early appraisals, (a) aspects of schizotypy have consistently been linked with higher rates of schizophrenia-spectrum traits and/or symptoms ( 5 7 ), (b) schizotypal personality has been further established as a key-element of the at risk mental state both in healthy high schizotypal individuals ( 8 ) and in individuals at clinical high risk for psychosis ( 9 ), and (c) the connection between schizotypy and schizophrenia-spectrum disorders was established over the years at several endophenotypic levels ( 10 17 ). Most importantly, high schizotypy has been associated with transition into schizophrenia ( 18 22 ).…”
Section: Introductionmentioning
confidence: 99%